2014
DOI: 10.3389/fimmu.2014.00511
|View full text |Cite
|
Sign up to set email alerts
|

Biology of the RANKL–RANK–OPG System in Immunity, Bone, and Beyond

Abstract: Discovery and characterization of the cytokine receptor-cytokine-decoy receptor triad formed by receptor activator of nuclear factor kappa-B ligand (RANKL)–receptor activator of NF-κB (RANK)–osteoprotegerin (OPG) have led not only to immense advances in understanding the biology of bone homeostasis, but have also crystalized appreciation of the critical regulatory relationship that exists between bone and immunity, resulting in the emergence of the burgeoning field of osteoimmunology. RANKL–RANK–OPG are member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
451
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 494 publications
(466 citation statements)
references
References 138 publications
(223 reference statements)
4
451
0
11
Order By: Relevance
“…Furthermore, the survival of dendritic cells is up-modulated in the presence of RANKL [24]. These observations led to the development of a concept in which bone and immune tissues were functionally interconnected and it is at the origin of the "osteoimmunology" [25,26]. The RANKL/RANK/OPG system is associated to the pathogenesis of osteosarcoma [27][28][29], directly through RANK on the osteosarcoma cell surface [30] and indirectly by regulating osteoclast activities [31] and the tumor vascularization [32].…”
Section: Cellular Heterogeneity Of the Osteosarcoma Microenvironmentmentioning
confidence: 99%
“…Furthermore, the survival of dendritic cells is up-modulated in the presence of RANKL [24]. These observations led to the development of a concept in which bone and immune tissues were functionally interconnected and it is at the origin of the "osteoimmunology" [25,26]. The RANKL/RANK/OPG system is associated to the pathogenesis of osteosarcoma [27][28][29], directly through RANK on the osteosarcoma cell surface [30] and indirectly by regulating osteoclast activities [31] and the tumor vascularization [32].…”
Section: Cellular Heterogeneity Of the Osteosarcoma Microenvironmentmentioning
confidence: 99%
“…By binding to RANKL, OPG inhibits the interaction of RANKL-RANK, thereby preventing RANK activation and subsequent osteoclastogenesis 13 . This system has also been reported to play roles in several cellular functions, which include apoptotic effect, immune response maintainance, and carcinogenesis 14,15 . Recently, studies showed that human OA chondrocytes also express and produce OPG, RANKL and RANK, and the molecular triad appears to be involved in OA progression 16 .…”
mentioning
confidence: 99%
“…M-CSF is important for proliferation and survival of the progenitor cells. Crucial for osteoclastogenesis is activation of receptor activator of NF-kB (RANK) expressed on osteoclast progenitors by receptor activator of NF-kB ligand (RANKL), an interaction that is inhibited by the decoy receptor osteoprotegerin (OPG) (1). The balance between pro-and antiosteoclastogenic cytokines regulating RANKL:OPG expression is suggested to drive inflammation-induced osteoclastogenesis (2)(3)(4)(5).…”
mentioning
confidence: 99%